Sulfur deficiency-induced genes affect seed protein accumulation and composition under sulfate deprivation - Aarabi, Fayezeh; Rakpenthai, Apidet; Barahimipour, Rouhollah; Gorka, Michal; Alseekh, Saleh; Zhang, Youjun; Salem, Mohamed A; Brückner, Franziska; Omranian, Nooshin; Watanabe, Mutsumi; Nikoloski, Zoran; Giavalisco, Patrick; et al. (Plant physiology (Bethesda), 2021)
Sulfur deficiency-induced proteins SDI1 and SDI2 play a fundamental role in sulfur homeostasis under sulfate-deprived conditions (-S) by downregulating glucosinolates. Here, we identified that besides glucosinolate regulation under -S, SDI1 downregulates another sulfur pool, the S-rich 2S seed storage proteins in Arabidopsis (Arabidopsis thaliana) seeds. We identified that MYB28 directly regulates 2S seed storage proteins by binding to the At2S4 promoter. We also showed that SDI1 downregulates 2S seed storage proteins by forming a ternary protein complex with MYB28 and MYC2, another transcription factor involved in the regulation of seed storage proteins. These findings have significant implications for the understanding of plant responses to sulfur deficiency.